CONTENT OF AMINO ACIDS IN PROTEIN AS A CRITERION OF MILK FORMULA QUALIT - E.Yu. Demkina ("Paediatrician" Publishers LLC, 2011)
The article describes the significance of amino acids' combination in protein and their excess or insufficiency in serum milk formulas for the health of infants. Results of evaluation of nutritive quality of proteins in experimental diets are presented.Key words: children, milk formula, protein, Prolacta.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (3): 97-102)